Recycled thermoplastics composites <Recycling parameters and recovered mechanical properties in novel thermoplastics sports composites> - Seah, Xin Yi (2016)
Carbon fibre composites are produced with Nylon matrix to study the recovered mechanical properties after recycling. In this project recycling of thermoplastic will be simulated by cutting/chipping single ply composite sheets into 3 different sizes of squares: 30mm, 20mm and 10mm then fabricated into laminates of 1.2mm thickness using hot pressing method. For comparison, references laminate of same thickness are made with virgin carbon fibre. Mechanical experiments were performed on the laminates which included impact strength, 3-point bending test and post-impact flexural test. In general terms, the results show no trend between the different chip sizes but the laminates show good potential in strength recovered as flexural strength shows about 30% decreases post-impact. This is important in sports industries as sports products are often being subjected to multiple uses and impact. To sum up, the mechanical properties recovered are up to 50% of Modulus and 70% in flexural strength. However, if this concept is to apply in sports product design, high variation in results must be taken into consideration.